Mycotoxins in Conversation With Bacteria and Fungi - Venkatesh, Nandhitha; Keller, Nancy P. (Frontiers in Microbiology, 2019)
An important goal of the mycotoxin research community is to develop comprehensive strategies for mycotoxin control and detoxification. Although significant progress has been made in devising such strategies, yet, there are barriers to overcome and gaps to fill in order to design effective mycotoxin management techniques. This is in part due to a lack of understanding of why fungi produce these toxic metabolites. Here we present cumulative evidence from the literature that indicates an important ecological role for mycotoxins, with a particular focus on Fusarium mycotoxins. Further, we suggest that understanding how mycotoxin levels are regulated by microbial encounters can offer novel insights for mycotoxin control in food and feed. Microbial degradation of mycotoxins provides a wealth of chemical information that can be harnessed for large-scale mycotoxin detoxification efforts.